Ethno-medicinal and Ayurvedic Approach in the Management and Treatment of Asthma (Swash Roga) - AVNISH K. UPADHYAY; KAUSHAL KUMAR (Dr. Chinmay Pandya, 2016)
In Ayurveda, Asthma is known as 'Shwas Roga'. Samprapti (Pathogenesis) of the Shwas Roga according to Ayurveda is the vitiated 'Pranvayu' combined with vitiated 'Kapha dosha' in the lungs causing obstruction in the 'Pranavaha srotasa' (Respiratory system). This results in gasping and laboured breathing which is known as 'Shwas Roga'. Asthma is a chronic illness involving the respiratory system in which the airway occasionally constricts, becomes inflamed, and is lined with excessive amounts of mucus, often in response to one or more triggers. These episodes precipitate by exposure to an environmental stimulant (or allergen), cold air, warm air, moist air, exercise or exertion, or emotional stress. Ayurvedic medicines are very safe and cure the problem to a great extent. Researchers of various disciplines are working on this problem to find out the solutions. Various modern means and measures have been discovered in this regard. Even then the effective drug without any side-effects has not been established yet. Ayurveda is the rich source of the therapeutic measures that can control the disease. Out of such therapeutic measures, various herbs, poly-herbal and herbo-mineral compounds were selected in different studies for the benefit of the increasing number of asthma patients and have been found to be effective. The aims of the present review are to establish the importance of Ethno-medicinal and Ayurvedic approach in the management and treatment of Asthma and explore any new interventions needed.